Coordination engineering of noble-metal clusters or single atoms supported on carbon for electrocatalytic water splitting - Wang, Qilun (Nanyang Technological University, 2022)
The electrochemical water splitting that can convert renewable electricity into storable hydrogen, a sustainable and clean energy carrier, provides an attractive strategy to mitigate the environmental pollution as well as energy crisis. For accelerating slow processes of oxygen evolution reaction (OER) and hydrogen evolution reaction (HER), constructing efficient catalysts have been motivated. In general, noble-metal cluster or single atom supported on carbon substrates have drawn tremendous research attention owing to specific d-orbital structure and tunable properties. Particularly, carbon as substrate not only offers a stabilizing and conductive matrix, but also impacts the electronic structure through interfacial interactions, necessitating a detailed understanding. In this thesis, I comprehensively investigate the role of coordination environment in tailoring electronic states of noble-metal nanoclusters or single atoms, as well as their further effect on adsorption energy of hydrogen and oxygenated intermediate species, based on probing experiments, operando spectroscopic measurements together with theoretical calculations. Firstly, I reported uniformly dispersed iridium nanoclusters embedded on nitrogen and sulfur co-doped graphene (Ir-NSG) to act as a pH-universal efficient and robust catalyst towards HER, comparable to Pt/C catalyst. Both the results of underpotentially deposited hydrogen and density functional theory (DFT) identified optimum hydrogen adsorption strength as the reason for the enhanced activity of Ir-NSG. Charge density difference analysis demonstrated that it was the electron transfer between Ir and the surficial N and S atoms that induced positively charged Ir sites, balancing the hydrogen adsorption/desorption behavior. Subsequently, to maximize the atomic efficiency of noble metal, I synthesized and compared HER activities of noble metal (including rhodium, ruthenium, iridium, palladium, and platinum)-based single-atom catalysts with various coordination environment (N, P and S), in which the Rh single-atom catalyst coordinated with both N and P (Rh1/NPG) exhibited the lowest overpotential due to its optimal H binding energy. More importantly, the uniform well-defined active sites of single atoms provided an ideal model platform to establish the relation between local coordination/electronic configurations with HER activities at atomic level, which could effectively guide the rational design of electrocatalysts. To promote another important half reaction of water splitting, I also investigated the effect of coordination environment of Ir nanoclusters on adsorption energy of oxygenated intermediates as well as OER activity. It was surprising to find that Ir-NSG also achieved an unprecedented pH-universal catalytic activity for OER and kept constant over a long continuous operation, far outperforming that of benchmark Ir/C catalyst. The low methanol oxidation onset potential implied a high adsorption energy of hydroxyl intermediate (OH*) on Ir sites coordinated with both N and S, which was beneficial for the binding of oxyhydroxide intermediate (OOH*) verified by DFT simulations. The operando X-ray absorption spectroscopy further unravelled higher oxidation states of surficial Ir sites accompanied by shorter Ir-O ligands during OER, facilitating the coupling of O-O bonds, which limited the whole reaction. As a conclusion, Ir-NSG displayed superb performance for overall water splitting when integrated directly as both anode and cathode electrodes at all pH values, requiring ultralow overpotentials at 10 mA cm−2 of 300, 190 and 220 mV in 1 M PBS, 0.1 M HClO4 as well as 1 M KOH electrolyte, respectively. My work proposed an appealing picture to develop efficient HER and OER catalysts, aiming to widespread utilization of practical water electrolyzers.